Inside BAR (The Biblical archaeology review, 1983)
Herod the Great, king of Israel from 37 to 4 B.C., transformed Judea architecturally into a Hellenistic-Roman realm that competed with the best in the empire. In this issue, BAR features three Herodian sites—Herodium, a wilderness palace-fortress where Herod was buried; Caesarea, where he built a great harbor; and a magnificent tomb-monument he built […]